A mercantilização da arte: o efeito das redes do social na mediação dos objetos - Bertani, Roberto (2013)
The present thesis focuses on the political dimension whose transversality relates to the relationship among art, the contemporary art market and the emergence of social medias. The empirical sample for this research makes use of the links between the market power and the cultural policy. In order to do so, the market of contemporary art from 2002 to the present time is studied, especially the one regarded two Brazilian artists in the international commercial scenario. As paradigm examples of those policies, this paper gives preference to the analysis of two artists Sergio Camargo and Adriana Varejão from around 1960 to 2012 by taking into account the relationship established between the growth and spread of those artistic and commercial phenomena by means of art auctions, exhibitions, fairs, publications and all the cultural and political system. This paper aims at analyzing the relationships among artistic expression, the market, the media and politics within the market of the Brazilian contemporary art; understanding how and why art which has a mobilizing potential and a significant power to affect subjectivities becomes a commodity for local and international consumption. The methodology not only highlights the historic perspective of the object but also the field procedures which focused on research and direct observations in national and international and national art fairs and auctions, analysis of the development of artworks, media, reports of international specialists, newspaper files, data base and others. The theoretical background was mainly obtained from authors, who contribute to the history of art, to the culture sociology, to cultural and social medias studies like Baudrillard (2008), Bourdie (1983,2003,2011), Latour (2000, 2003, 2011), Law (1992) among others. The analysis conducted at the end of the research supports the initial thesis that the contemporary art market, as well as its subjacent symbolic apparatus, through marketing strategies and media tools is being transformed in artistic capital by commercial policy makers for economic purpose.